Evolutionary Dynamics of Begomoviruses and Its Satellites Infecting Papaya in India - Srivastava, Aarshi; Pandey, Vineeta; Sahu, Anurag Kumar; Yadav, Dinesh; Al-Sadi, Abdullah M.; Shahid, Muhammad Shafiq; Gaur, R. K. (Frontiers in Microbiology, 2022)
The genus Begomovirus represents a group of multipartite viruses that significantly damage many agricultural crops, including papaya, and influence overall production. Papaya leaf curl disease (PaLCD) caused by the complex begomovirus species has several important implications and substantial losses in papaya production in many developing countries, including India. The increase in the number of begomovirus species poses a continuous threat to the overall production of papaya. Here, we attempted to map the genomic variation, mutation, evolution rate, and recombination to know the disease complexity and successful adaptation of PaLCD in India. For this, we retrieved forty-four DNA-A and twenty-six betasatellite sequences from GenBank reported from India. An uneven distribution of evolutionary divergence has been observed using the maximum-likelihood algorithm across the branch length. Although there were phylogenetic differences, we found high rates of nucleotide substitution mutation in both viral and sub-viral genome datasets. We demonstrated frequent recombination of begomovirus species, with a maximum in intra-species recombinants. Furthermore, our results showed a high degree of genetic variability, demographic selection, and mean substitution rate acting on the population, supporting the emergence of a diverse and purifying selection of viruses and associated betasatellites. Moreover, variation in the genetic composition of all begomovirus datasets revealed a predominance of nucleotide diversity principally driven by mutation, which might further accelerate the advent of new strains and species and their adaption to various hosts with unique pathogenicity. Therefore, the finding of genetic variation and selection emphases on factors that contribute to the universal spread and evolution of Begomovirus and this unanticipated diversity may also provide guidelines towards future evolutionary trend analyses and the development of wide-ranging disease control strategies for begomoviruses associated with PaLCD.